Transcriptome Profiling and Identification of the Candidate Genes Involved in Early Ripening in Ziziphus Jujuba - Li, Baiyun; Li, Hui; Xu, Zehua; Guo, Xinnian; Zhou, Tao; Shi, Jiangli (Frontiers in Genetics, 2022)
The early ripening jujube is an immensely popular fresh fruit due to its high commercial value as well as rich nutrition. However, little is known about the mechanism of jujube fruit’s ripening. In this study, the transcriptome profiles were comprehensively analyzed between the ‘Lingwu Changzao’ jujube and its early-ripening mutant during the fruit development and maturity. A total of 5,376 and 762 differentially expressed genes (DEGs) were presented at 80 and 90 days after the flowering of the jujube fruit, respectively. Furthermore, 521 common DEGs were identified as candidate genes that might be associated with the fruit’s early ripening. Our findings demonstrated that in a non-climacteric jujube fruit, abscisic acid (ABA) was more greatly involved in fruit ripening than ethylene. Meanwhile, the fruit ripening of the early-ripening mutant was regulated by eight promotors of DEGs related to glucose and fructose, seven repressors of DEGs related to brassinosteroid signal transduction, and a series of transcription factor genes (MYB, Bhlh, and ERF). Additionally, the expression of 20 candidate DEGs was further validated by real-time PCR during the late fruit maturation stage. Collectively, the present study sheds light on the metabolic mechanism of the fruit’s early ripening and provides valuable candidate genes for the early-ripening mutant’s breeding.